2020
DOI: 10.1002/aelm.202000452
|View full text |Cite
|
Sign up to set email alerts
|

Catechol‐Based Molecular Memory Film for Redox Linked Bioelectronics

Abstract: Recent biological research has demonstrated that redox is an independent biological-signaling modality. [1-8] This redox signaling modality is best understood in host-pathogen immune interactions where an oxidative burst generates a set of reactive species (e.g., reactive oxygen species) that can sometimes be transduced into second messengers (i.e., reactive electrophiles) [4] and ultimately alters biological function through post-translational protein modification (e.g., conversion of protein cysteine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 52 publications
4
50
0
Order By: Relevance
“…Previous studies have assigned this peak to the oxidized quinone (Q) moieties. [ 26 ] The rightmost plot in Figure 3a shows the change in absorbance measured at 480 nm (Δ| A 480 |) decreased with time, and this change was larger for films written with a larger number of electrode writing strokes. These results indicate that: i) ascorbate can donate electrons to the film to convert the oxidized quinone moieties (Q‐state) into reduced catechol moieties (QH 2 ‐state); ii) the film's capacity to accept electrons can be adjusted by the extent of catechol modification; and iii) electron transfer to the film can be “passively” observed (i.e., without changing the state) by measuring optical absorbance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have assigned this peak to the oxidized quinone (Q) moieties. [ 26 ] The rightmost plot in Figure 3a shows the change in absorbance measured at 480 nm (Δ| A 480 |) decreased with time, and this change was larger for films written with a larger number of electrode writing strokes. These results indicate that: i) ascorbate can donate electrons to the film to convert the oxidized quinone moieties (Q‐state) into reduced catechol moieties (QH 2 ‐state); ii) the film's capacity to accept electrons can be adjusted by the extent of catechol modification; and iii) electron transfer to the film can be “passively” observed (i.e., without changing the state) by measuring optical absorbance.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to detecting the pattern of the catechol that was irreversibly written into the film (Figure 2), it is also possible to detect the reversible switching of this catechol's redox state. To demonstrate optical detection of the redox‐state of the patterned catechol regions, [ 26 ] we started with a Chit 0 /agarose hydrogel that was patterned with two circular dots with the same extent of modification ( Q fab = 5 mC), and locally set the redox state of these dots to an oxidized (Q) state or a reduced (QH 2 ) state through mediated electrochemistry as illustrated in Figure a. Experimentally, the catechol‐patterned Chit 0 /agarose hydrogel film was immersed in Fc/Ru 3+ mediator solutions (0.1 m m each), a standard gold electrode was placed above each dot, and the imposed voltage was controlled to set the redox state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular redox in particular has proven to be a valuable source of cellular information that is easily accessible to human and device readable outputs. For example, detection and memory of redox state was achieved using a chatecol-chitosan-agarose matrix with optical or electrical output 59 . The ubiquitous nature of biological redox has made it possible to electronically interact with skin pigments such as melanin, control biological patterning and gene expression, and integrate two-way communication via redox stress signals 60 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, redox-inactive materials can be conjugated with redox mediators such as catechols and quinones, and these are easily fabricated at discrete locations ( Liu et al., 2010 ). We have suggested that these materials can serve as a form of bioelectronic memory to locally address where specific communication events happen within a spatial domain, such as within the spatial resolution of an electrode array or gel ( Wu et al., 2020 ). That is, in these storage devices, a non-conducting material, such as catechol-modified chitosan, serves as a redox sink to sequester electrons away from the electrode.…”
Section: Introductionmentioning
confidence: 99%